Music Composition Tegak Anyar | Komposisi Musik Tegak Anyar - I Wayan Yudiarta (Pusat Penerbitan LPPMPP ISI Denpasar, 2022)
The stylist's interest in muerupat patets is one of the reasons behind this work. If accumulated, each patet has its own 3(ding), 4(dong), 5(deng), 7(dung) and 1(dang) notes. It means that in seven patets, the stylist gets seven notes of 3 (ding), seven notes of 4 (dong) and so on until tone 1 (dang). In addition, the stylist sees an opportunity where recently there has been no work using the media, revealing the gamelan Semar Pegulingan Saih Pitu with the title Tegak Anyar. Tegak Anyar is formed from two syllables, namely Upright and Anyar, where Tegak means sitting, there is also a language term, namely space or land and Anyar means new. Tegak Anyar means that the stylist wants to provide a new space for the media that the stylist uses, namely Semar Pegulingan Saih Pitu with a new percussion form. The stylist imagines to process the patets contained in the gamelan Semar Pegulingan Saih Pitu. In general, the use of these patets is used to change the atmosphere, because each patet has a different sound impression. The stylist's main goal is to invite the public to know how the development of Balinese musical art is with the benefit of enriching Balinese musical colors and providing new breakthroughs in their work. This work uses a method created by Alma M. Hawkins in the book Creating Trough Dance. Where the creation of a work of art needs to use three stages, namely exploration, improvisation and formation. The work of Tegak Anyar is realized in the form of Creative Tabuh which considers the element of musicality.